Perusterveydenhuollon ammattilaisten kokemuksia potilaiden työkyvyn tuen tarpeen systemaattisesta tunnistamisesta ja työkykykoordinaattoritoiminnasta. - VÄHÄTALO, LAURI; SIUKOLA, ANNA; NURMI, HANNA; REHO, TIIA; VILJAMAA, MERVI; ATKINS, SALLA; SUMANEN, MARKKU; SAUNI, RIITTA (Hoitotiede, 2025)
A trial was conducted in public primary health care where professionals systematically assessed whether the patient had need for work ability support or the visit related to work. Based on this recognition patients were guided to a work ability coordinator. This interview study examines professionals' experiences of the trial. The data consisted of 12 interviews with public primary health care professionals, which were conducted at the end of 2021. Data were analyzed with inductive thematic analysis. Recognition of need for work ability support was considered necessary and easy if it was conducted during suitable consultations. Participants requested increased communication about the trial and patient referral. Work ability coordinators were seen as important, but their roles remained obscure. The systematic recognition of need for work ability support in public primary health care appears to be possible and plausible, but the professionals' opinions should be considered during planning. Work ability coordinators may reduce the guidance and investigation work of professionals.